DIGITAL TECHNOLOGY INTEGRATION IN TEXT-BASED ENGLISH FOR FRONT OFFICE INSTRUCTION IN VOCATIONAL TOURISM EDUCATION: A MIXED METHOD STUDY - Ni Putu Era Marsakawati; Rima Andriani Sari; I Ketut Armawan; Putu Ayu Prabawati Sudana (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study investigates how digital technology is integrated into text-based English for Front Office (EFO) instruction to support language literacy, digital literacy, and employability skills in vocational tourism education. The integration of digital technology in English for Specific Purposes (ESP) has often been tool-oriented, with limited attention to teachers’ pedagogical practices in vocational contexts. The study employed a mixed-method design with an explanatory sequential approach involving 20 English teachers from vocational tourism schools. Data were collected through questionnaires, interviews, and document analysis. The data were analyzed using descriptive statistics and thematic analysis. The findings reveal that teachers utilize various digital technologies, including learning management systems, presentation tools, communication applications, video editing tools, virtual tours, and AI-based applications. These technologies are integrated through multimodal literacy practices such as role-play simulations, video projects, virtual tour narratives, and interactive assessments that engage students in reading, writing, speaking, and digital meaning-making. However, teachers face challenges related to limited infrastructure, varying levels of digital literacy competence, student motivation, and increased instructional workload. The study concludes that pedagogically grounded digital technology integration enhances text-based EFO learning by supporting language literacy and digital literacy in authentic workplace contexts. The findings imply the need for continuous teacher professional development and institutional support to promote sustainable literacy-oriented digital pedagogy in vocational tourism education. This study contributes to literacy-oriented ESP pedagogy by foregrounding teachers’ digital pedagogical practices in vocational tourism education.